2022
DOI: 10.3390/ijerph19074363
|View full text |Cite
|
Sign up to set email alerts
|

Life Conditions as Mediators of Welfare State Effect on Mental Wellbeing among Oldest Old in Europe

Abstract: Background: Mental wellbeing is formed by our daily environments, which are, in turn, influenced by public policies, such as the welfare state. This paper looks at how different aspects of life conditions may mediate the welfare state effect on mental wellbeing in oldest old age. Methods: Data were extracted from Round 6 of the European Social Survey (2012). The dataset comprised of 2058 people aged 80 years and older from 24 countries. Mediation analyses determined possible links between the welfare state, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Mental health by social expenditure Mental wellbeing. Concerning the positive aspects of mental health, studies examined the relationship between social expenditure and life satisfaction (Clench-Aas and Holte, 2018;Nordheim and Martinussen, 2019;Dumbraveanu, 2015;Flavin et al, 2011;Hessami, 2010;Knoll and Pitlik, 2016) happiness (Ono and Lee, 2013) and wellbeing (Cresswell-Smith, 2022). Overall, the evidence offers support for the positive link between higher social expenditure and mental well-being, with positive relationships reported in six studies (Clench-Aas and Holte, 2018;Cresswell-Smith, 2022;Dumbraveanu, 2015;Flavin et al, 2011;Hessami, 2010;Nordheim and Martinussen, 2019), negative effects were reported in one paper (Knoll and Pitlik, 2016) and one study described a more controversial picture (Ono and Lee, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Mental health by social expenditure Mental wellbeing. Concerning the positive aspects of mental health, studies examined the relationship between social expenditure and life satisfaction (Clench-Aas and Holte, 2018;Nordheim and Martinussen, 2019;Dumbraveanu, 2015;Flavin et al, 2011;Hessami, 2010;Knoll and Pitlik, 2016) happiness (Ono and Lee, 2013) and wellbeing (Cresswell-Smith, 2022). Overall, the evidence offers support for the positive link between higher social expenditure and mental well-being, with positive relationships reported in six studies (Clench-Aas and Holte, 2018;Cresswell-Smith, 2022;Dumbraveanu, 2015;Flavin et al, 2011;Hessami, 2010;Nordheim and Martinussen, 2019), negative effects were reported in one paper (Knoll and Pitlik, 2016) and one study described a more controversial picture (Ono and Lee, 2013).…”
Section: Resultsmentioning
confidence: 99%